2016
DOI: 10.4025/jphyseduc.v27i1.2152
|View full text |Cite
|
Sign up to set email alerts
|

Voleibol Masculino De Alto Nível: Associação Entre as Ações De Jogo No Side-Out

Abstract: RESUMO ABSTRACTThe aim of this study was to analyse the game practiced in the side-out Men's Volleyball Superliga 2014/2015. The sample was composed by 12 teams and it was analyzed 142 games, totaling 19,545 reception, setting and attack actions. The results showed the association between the effect of reception and attack location; effect of reception and attack time; effect of reception and attack effect; effect of attack location and attack time; effect of attack location and effect attack and effect of att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 20 publications
5
21
1
2
Order By: Relevance
“…Dentre os fundamentos, a literatura vem evidenciando o ataque como a ação que mais influencia na conquista dos pontos e no resultado final da partida (13,33,46) , sendo necessário que a construção ofensiva, quando há condições ideais de distribuições, ocorra com quatro atacantes (15) . Entretanto, uma vez que a distribuição do levantador se mostra dependente da qualidade da receção (21) , da disponibilidade dos atacantes (3) e da disposição dos bloqueadores (7) , observa-se a tendência de maior solicitação dos atacantes das extremidades da rede, principalmente dos atacantes da zona 4 (15,42,44) , tal como atestado pelos dados estatísticos da Superliga Brasileira de 2014/ 2015, onde 34% dos ataques foram realizados da zona 4.27% da zona 2.24% da zona 3, 10% da zona 1 e 5% da zona 6 (12) .…”
Section: Introductionunclassified
“…Dentre os fundamentos, a literatura vem evidenciando o ataque como a ação que mais influencia na conquista dos pontos e no resultado final da partida (13,33,46) , sendo necessário que a construção ofensiva, quando há condições ideais de distribuições, ocorra com quatro atacantes (15) . Entretanto, uma vez que a distribuição do levantador se mostra dependente da qualidade da receção (21) , da disponibilidade dos atacantes (3) e da disposição dos bloqueadores (7) , observa-se a tendência de maior solicitação dos atacantes das extremidades da rede, principalmente dos atacantes da zona 4 (15,42,44) , tal como atestado pelos dados estatísticos da Superliga Brasileira de 2014/ 2015, onde 34% dos ataques foram realizados da zona 4.27% da zona 2.24% da zona 3, 10% da zona 1 e 5% da zona 6 (12) .…”
Section: Introductionunclassified
“…In addition, the studies did not distinguish the effect of the attack according to the effect of reception, which may entail a decontextualized game analysis, since the effect of reception limits the options of setting and the construction of the attack (Costa et al 2016b). In this way, it is necessary to analyse the attack situations that present similar initial contexts, allowing finding the predictive factors of the attack for each specific game scenario.…”
Section: Predictive Factors Of Back Row Attack | 59mentioning
confidence: 99%
“…To analyse the type of attack, an adaptation of the instrument proposed by Costa et al (2011Costa et al ( , 2016b, was used. The attacks that hit the blocking with power were grouped to strong attacks in parallel or diagonal, according to the trajectory of the ball, while the soft attacks that hit the blocking were grouped to the category off-speed attack.…”
Section: Types Of Attackmentioning
confidence: 99%
“…To analyze the type of attack, an adaptation of the instrument proposed by Costa et al 13,17 was used. Attacks exploiting the blockage, when carried out with power were grouped into powerful parallel or diagonal attacks, according to the trajectory of the ball, while placed attacks that explored the blockade were grouped into placed attacks category.…”
Section: Variablesmentioning
confidence: 99%
“…Volleyball surveys have sought to understand the game in terms of the final result of the game [5][6] , the position of the team at the end of the competition [7][8] and type of game [9][10] , showing that high performance levels in serve 5 , attack 11 , and block 7 can predict success in the game. In this context, studies have shown that attack was the fundamentals that most influenced the conquest of scores and the final result of the game 12 , requiring that the offensive construction, when there are ideal conditions of distributions, occurs with four attackers 13 . However, researches were mostly focused on the general understanding of the game practiced, specifically the effectiveness of actions 11,14 , disregarding the situational constraints imposed on the different situational scenarios.…”
Section: Introductionmentioning
confidence: 99%